2009
DOI: 10.1152/japplphysiol.91446.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to high-intensity intermittent exercise in rodents

Abstract: In humans, exercise-induced plasma volume (PV) expansion is typically associated with an increase in plasma albumin content, due in part to an increase in hepatic albumin synthesis. We tested the ability of a 12-day high-intensity intermittent exercise protocol to induce an increase in PV in rodents. Since albumin synthesis is transcriptionally regulated, we tested the hypothesis that exercise training would induce an increase in hepatic albumin gene expression. Fifty adult male Sprague-Dawley rats weighing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Our results cannot conclusively determine the precise mechanisms leading to increased endurance capacity, but the differences in endurance were associated with corresponding differences in haematocrit and SO fibre CSA in two key locomotor muscles. The higher haematocrit in endurance-trained lizards is consistent in its directional change to studies of humans and other mammals (reviewed in Bexfield et al, 2009;Connes et al, 2013), as well as birds (Riera et al, 1983), crocodilians (Eme et al, 2009) and fishes (Beamish, 1978), and locomotor endurance in lizards is related to haematocrit (Garland, 1984;. The increased oxygen-carrying capacity that comes with higher haematocrit may explain a significant portion of the increase in endurance.…”
Section: Discussionmentioning
confidence: 59%
“…Our results cannot conclusively determine the precise mechanisms leading to increased endurance capacity, but the differences in endurance were associated with corresponding differences in haematocrit and SO fibre CSA in two key locomotor muscles. The higher haematocrit in endurance-trained lizards is consistent in its directional change to studies of humans and other mammals (reviewed in Bexfield et al, 2009;Connes et al, 2013), as well as birds (Riera et al, 1983), crocodilians (Eme et al, 2009) and fishes (Beamish, 1978), and locomotor endurance in lizards is related to haematocrit (Garland, 1984;. The increased oxygen-carrying capacity that comes with higher haematocrit may explain a significant portion of the increase in endurance.…”
Section: Discussionmentioning
confidence: 59%
“…Both LE and SD rats trained on running wheels had significantly elevated levels of %fluid compared with sedentary rats. It has been shown that rats subjected to repeated exercise training undergo an increase in plasma volume (2). The well-known expansion in plasma volume with exercise in humans is attributed to an increase in plasma content of albumin that acts to retain water (2,4,7).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that rats subjected to repeated exercise training undergo an increase in plasma volume (2). The well-known expansion in plasma volume with exercise in humans is attributed to an increase in plasma content of albumin that acts to retain water (2,4,7). With significantly elevated %fluid levels in wheel-trained rats, we expected that recovery from an injected bolus of normal or hypertonic saline would differ from that of sedentary animals.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 1 month of exercise increased liver iron stores and blood Hb and enhanced iron absorption. The increased Hb, without changes in Hct, in the exercising rats' blood reflect a much greater amount of Hb, and a greater circulating erythrocytes mass than in sedentary animals, most likely as a result of the expanded blood volume induced by exercise [33]. This increased erythrocyte mass with accelerated Hb synthesis and erythrocyte turnover [1,19,20] implied that erythropoiesis must be extremely active and requires more iron for Hb synthesis.…”
Section: Discussionmentioning
confidence: 99%